The Relationship Between Physical Activity and Body Mass Index on Functional Ability Elderly Women in Jegu Village, Penebel, Tabanan - I Made Yoga Parwata; Luh Putu Ayu Vitalistyawati; Ni Putu Dwi Larashati; Ni Luh Made Narisa Pradnyasari (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2025)
Functional ability is an important indicator in determining the level of independence of older adults in performing daily activities. Low physical activity and non-ideal body mass index (BMI) have the potential to reduce functional ability, especially in older women who experience physiological changes due to aging and hormonal shifts after menopause. This study aimed to determine the relationship between physical activity and BMI with functional ability in older women in Jegu Village. This research used a quantitative approach with a cross-sectional analytic design. The sample consisted of 64 older women aged 60–74 years, selected through purposive sampling. Physical activity was measured using the Physical Activity Scale for the Elderly (PASE), functional ability was assessed using the Barthel Index, and BMI was calculated based on weight and height. Data were analyzed using Spearman’s correlation test and multiple correlation analysis. The results show a significant positive relationship between physical activity and functional ability (p = 0.000; r = 0.783), and a significant negative relationship between BMI and functional ability (p = 0.002; r = –0.376). The multiple correlation analysis shows a significant relationship between physical activity and BMI simultaneously with functional ability (p = 0.000; R = 0.723; R² = 0.523), with physical activity being the dominant factor. It can be concluded that there is a strong relationship between physical activity and BMI with the functional ability of older women in Jegu Village.